Distributed manufacturing systems with digital agents - Herakovič, Niko (Strojniški vestnik, 2019)
This paper presents a novel approach to implement manufacturing nodes using the combined strength of digital twins, holons, and digital agents. Manufacturing nodes are based on holon theory and present a universal manufacturing platform that consists of cyber-physical systems (CPS) with an integrated digital twin, digital agent, databases and various communication protocols. The manufacturing node network is controlled globally using the global digital twin of logistics process and locally using the local nodes and local digital agents, digital twins and information shared by the node network. The main objective of this research was to develop and test a new concept of distributed system modelling and distributed system control for easy implementation of distributed manufacturing nodes in a smart factory concept.
Keywords: communication; digital twins; digitalni agenti; digitalni dvojčki; distribuirani sistemi; distributed control; holoni; izmenjava podatkov; nodes; pametne tovarne; smart factories; vozlišča